2004
DOI: 10.1128/iai.72.7.3902-3906.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Ami-AliA/AliB Permease of Streptococcus pneumoniae Is Involved in Nasopharyngeal Colonization but Not in Invasive Disease

Abstract: The Ami-AliA/AliB oligopeptide permease is an ATP-binding cassette transporter which is found in Streptococcus pneumoniae and which is involved in nutrient uptake. We investigated the role of the three paralogous oligopeptide-binding lipoproteins AmiA, AliA, and AliB by using murine models of pneumococcal colonization and invasive disease. A series of mutants lacking aliA, aliB, and amiA either alone or in combination as double or triple mutations were used. Inoculation of the nasopharynx with a mixture of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 15 publications
1
79
1
Order By: Relevance
“…Many studies have shown that expression of pneumococcal proteins during pathogenesis is required at different stages of infection (15,21,25). One study, performed by Oggioni and coworkers, presents evidence that the "transcriptional state" of the pneumococcal cells differs at particular niches within the host (24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have shown that expression of pneumococcal proteins during pathogenesis is required at different stages of infection (15,21,25). One study, performed by Oggioni and coworkers, presents evidence that the "transcriptional state" of the pneumococcal cells differs at particular niches within the host (24).…”
Section: Discussionmentioning
confidence: 99%
“…Nine-week-old female outbred CD-1 mice (Harlan, Horst, Netherlands) were used for all infection models. Prior to the infection experiments, D39 wild-type and mutant strains were passaged in mice as described previously (15). Cultures of mouse-passaged S. pneumoniae strains were grown to an optical density at 600 nm of 0.3 and stored in aliquots at Ϫ80°C in 10% glycerol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Signature-tagged mutagenesis has identified putative virulence factors specific for pneumonia (33) and for colonization of mucosal surfaces (18). An ATP-binding cassette transporter, the Ami-AliA/AliB permease, has been shown to be important for colonization and not invasive disease in a mouse model of infection (22). In addition to tissuespecific virulence factors, new research indicates that specific virulence factors are important for transition between tissue sites (29).…”
Section: Resultsmentioning
confidence: 99%